Metallic Lewis acids-catalyzed acetylation of alcohols with acetic anhydride and acetic acid in ionic liquids: study on reactivity and reusability of the catalysts - Lee, SG; Park, JH (ELSEVIER, 2003)
The catalytic activity and reusability of the metallic Lewis acids, Cu(OTf)(2), Yb(OTf)(3), Sc(OTf)(3), In(OTf)(3), HfCL4 . (THF)(2) and InCl3, for acetylation of alcohols with acetic anhydride and acetic acid has been examined in environmentally benign room temperature ionic liquids, [bmim][X] (bmim = 1-n-butyl-3-methylimidazolium, X = PF6, BF4, SbF6). All of the catalysts effectively catalyzed the acetylation with acetic anhydride in an ionic liquid, [bmim][PF6]. In direct acetylation with acetic acid, Yb(OTf)(3), Sc(OTf)(3) and InCl3 showed excellent catalytic activity in the [bmim] [PF6] ionic liquid and were reasonably recycled. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: MANNICH-TYPE REACTION; 3 COMPONENT SYNTHESIS; SCANDIUM TRIFLUOROMETHANESULFONATE; ACYLATION; EFFICIENT; CONDENSATION; TRIFLATE; AMINES